2004
DOI: 10.1093/jnci/djh074
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Oral Exfoliated Cells and Risk of Head and Neck Cancer

Abstract: Infection of oral exfoliated cells with HPV-HR types is a risk factor for head and neck cancer, independent of alcohol and tobacco use, and acts synergistically with alcohol consumption. HPV testing of an oral rinse may be predictive of an HPV-related head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
189
8
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(227 citation statements)
references
References 27 publications
20
189
8
10
Order By: Relevance
“…Here, we prefer to the latter classification. Unlike some other studies that analyze for oral cancer other than oropharyngeal site showed low prevalence and non significant association between HPV and oral cancer (Smith et al, 2004), our data indicated that HPV is highly-associated with oral cancer (including oral cavity and oropharyngeal site) and act as an independent risk factor combined with other risk factors such as tobacco and alcohol.…”
Section: Li-li Gan Et Alcontrasting
confidence: 96%
See 1 more Smart Citation
“…Here, we prefer to the latter classification. Unlike some other studies that analyze for oral cancer other than oropharyngeal site showed low prevalence and non significant association between HPV and oral cancer (Smith et al, 2004), our data indicated that HPV is highly-associated with oral cancer (including oral cavity and oropharyngeal site) and act as an independent risk factor combined with other risk factors such as tobacco and alcohol.…”
Section: Li-li Gan Et Alcontrasting
confidence: 96%
“…A meta-analysis (1988Jemal et al, -2007 showed that the prevalence of HPV DNA in OSCC was 38.1% (Termine et al, 2008). HPV-16 genomic DNA can be detected in 16.5% to 19% of oral cancers in the USA (Schwartz et al, 1998;Smith et al, 2004). While the meta-analysis of Chinese population indicated that the overall rate of HPV-positive OSCC was 58.0% and HPV-16 infection accounted for 47.47% of OSCC (Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to date, only in tonsillar squamous cell carcinoma has the morphology of HPV-positive tumors has suggested that HPV may have a predilection for a population of nonkeratinized squamous cells, easier to penetrated especially in the presence of alcohol, or that the virally transformed cells inhibit keratinization of the tumor cells. 68 This latter hypothesis is consistent with the results of Smith et al, 69 who consider HR HPV infection of oral exfoliated cells to be a risk factor for head-and-neck squamous cell carcinoma, independent of alcohol and tobacco use. Furthermore, Smith et al 70 observed a significant interaction effect between younger age and heavy alcohol use associated with HR HPV cancer status.…”
Section: Discussionsupporting
confidence: 86%
“…This is in contrast with the reports in subjects with oral cancer, suggesting that there may be other factors that favor HPV-16 survival in such environment (Smith et al, 2004). Both HPV-16 and HPV-18 were found in one positive sample.…”
Section: Discussioncontrasting
confidence: 86%